2022
DOI: 10.1021/acsami.2c01310
|View full text |Cite
|
Sign up to set email alerts
|

Shape-Recoverable Hyaluronic Acid–Waterborne Polyurethane Hybrid Cryogel Accelerates Hemostasis and Wound Healing

Abstract: Wound dressings that promote quick hemostasis and are highly efficient in healing wounds are urgently needed to meet the increase in clinical demands worldwide. Herein, a dihydrazide-modified waterborne biodegradable polyurethane emulsion (PU-ADH) and oxidized hyaluronic acid (OHA) were autonomously cross-linked to form a hybrid hyaluronic acid–polyurethane (HA-PU) cryogel by hydrazone bonding at −20 °C. Through its specific macroporous structure (which is approximately 220 μm) constructed by aggregated PU-ADH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 49 publications
0
35
0
Order By: Relevance
“…Varieties of strategies have been proposed to enhance the wet adhesion of ionic hydrogels via tailoring the quantities and positions of the charges, ion strength, or pH of aqueous solution. ,, Additionally, the hydrogels with wet adhesion are often applied in hemostasis. Hemostasis can be obtained by varieties of mechanisms, including physical adhesion to the tissue, chemical (such as electrostatic) interactions and bonding to coagulation factors, and absorption of plasma. Recently, much progress has been achieved in hemostasis, such as using shape-recoverable hydrogel to accelerate hemostasis, enzyme-responsive in situ polymerization of hydrogels for hemostasis, and snake extract-laden hydrogel for hemostasis . Importantly, one of the strategies for hemostasis is to develop wet-adhesive hydrogels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Varieties of strategies have been proposed to enhance the wet adhesion of ionic hydrogels via tailoring the quantities and positions of the charges, ion strength, or pH of aqueous solution. ,, Additionally, the hydrogels with wet adhesion are often applied in hemostasis. Hemostasis can be obtained by varieties of mechanisms, including physical adhesion to the tissue, chemical (such as electrostatic) interactions and bonding to coagulation factors, and absorption of plasma. Recently, much progress has been achieved in hemostasis, such as using shape-recoverable hydrogel to accelerate hemostasis, enzyme-responsive in situ polymerization of hydrogels for hemostasis, and snake extract-laden hydrogel for hemostasis . Importantly, one of the strategies for hemostasis is to develop wet-adhesive hydrogels.…”
Section: Introductionmentioning
confidence: 99%
“…Hemostasis can be obtained by varieties of mechanisms, including physical adhesion to the tissue, chemical (such as electrostatic) interactions and bonding to coagulation factors, and absorption of plasma. 33−35 Recently, much progress has been achieved in hemostasis, such as using shape-recoverable hydrogel to accelerate hemostasis, 36 enzyme-responsive in situ polymerization of hydrogels for hemostasis, 37 and snake extract-laden hydrogel for hemostasis. 38 Importantly, one of the strategies for hemostasis is to develop wet-adhesive hydrogels.…”
Section: Introductionmentioning
confidence: 99%
“…2f showed that a higher rate of water uptake in the dried TA@GelMA hydrogel coating compared to the dried GelMA hydrogel and no significant differences were existed in the SRs between two wet hydrogel coating groups. Evidences [ 49 , 50 ] demonstrated that the faster swelling capacity of hydrogels coating endowed the complexes to concentrate coagulation factors in shorter time, which was more conducive to hemostasis. The freeze-dried hydrogel-mesh complexes, which are more suitable for storage in vacuum packages compared to wet complexes, can absorb water molecules in a very short time and convert them into wet complexes better for cell attachment and proliferation.…”
Section: Resultsmentioning
confidence: 99%
“… Materials Hemostatic mechanism Characteristic applications Limitation Polysaccharide-derived Hemostatic Materials Chitosan and its derivatives Positively charged amino; Erythrocyte aggregation; Platelet adhesion Hemostasis of rat liver and femoral artery trauma [ 62 ]; Bio-adhesion on rat liver and beating heart, hemostasis of rat liver hemorrhage [ 60 ] Poor solubility Cellulose and its derivatives Concentration effect; Negatively charged carboxyl; Complexation with Fe 3+ ; Platelet activation and aggregation Hemostasis of rabbit liver and ear artery hemorrhage [ 70 ]; Hemostasis of rat liver and Swine femoral artery injury [ 68 ] Weak pro-healing bioactivity; Potential acidosis risk Alginate and Hyaluronic Acid Concentration effect; Negatively charged carboxyl; Activating intrinsic pathway Hemostasis of rat liver hemorrhage, shape-recovery ability, wound healing [ 74 ]; Hemostasis of liver hemorrhage in normal and hemophilia mice, prevention of abdominal adhesion [ 77 ] Low hemostatic ability; Insufficient chemical stability Polypeptide-derived Hemostatic Materials Collagen Platelet activation; Activating intrinsic pathway Promotive capacity of blood cell adhesion, hemostasis of rabbit liver injury [ 82 ]; Minimal proinflammatory cytokine production, platelet adhesion and activation [ 83 ] Heterogeneity; Immunogenicity risk Silk fibroin Platelet aggregation and adhesion; Enhanced binding of platelets and fibrinogen Wet tissue adhesion, Hemostasis of rabbit ear artery, liver, cardiac puncture, and femoral artery injury, hemostasis of rat liver, heart and tail bleeding [ 95 ] Insufficient chemical stability Keratin Platelet adhesion; Activating intrinsic and extrinsic pathways; Promoting fibrin clotting Hemostasis of rat liver puncture and tail amputation injury [ 101 ]; Hemostasis of rat liver puncture and femoral artery injury [ 104 ] Heterogeneity; Complex keratin-related proteins …”
Section: Molecular Structure Design Of the Hemostasis Materialsmentioning
confidence: 99%